Wide-Band Wide-Beam Circularly-Polarized Slot-Coupled Antenna for Wide-Angle Beam Scanning Arrays - Marco Salucci; Giacomo Oliveri; Mohammad Abdul Hannan; Renzo Azaro; Andrea Massa (Sensors, 2023)
The design of a wide-band wide-beam circularly-polarized slot-coupled (WWCS) radiating element for wide-angle scanning arrays (WASAs) is addressed. The WWCS radiator exploits a simple geometry composed of a primary (driven) and a secondary (passive) element to generate wide-beam patterns with rotational symmetry and high polarization purity. The synthesis was carried out by means of a customized version of the System-by-Design (SbD) method to derive a WWCS radiator with circular polarization (CP) and wide-band impedance matching. The results of the numerical assessment, along with a tolerance analysis, confirm that the synthesized WWCS radiating element is a competitive solution for the implementation of large WASAs. More specifically, a representative design working at <semantics>f0=2.45</semantics> [GHz] is shown having fractional bandwidth <semantics>FBW≃15%</semantics>, half-power beam-width <semantics>HPBW<mfenced separators="" open="(" close=")">f0</mfenced>≃180</semantics> [deg] in all elevation planes, and high polarization purity with broadside axial ratio <semantics>AR<mfenced separators="" open="(" close=")">f0</mfenced>=3.2</semantics> [dB] and cross-polar discrimination <semantics>XPD<mfenced separators="" open="(" close=")">f0</mfenced>=15</semantics> [dB]. Finally, the experimental assessment, carried out on a PCB-manufactured prototype, verifies the wide-band and wide-beam features of the designed WWCS radiator.